Highly Efficient Synthesis of 3,3-Disubstituted Oxindoles through Direct Oxidative Alkylarylation of N-Arylacrylamides with Simple Alkanes - Chen, Yan; Song, Weihong; Zhou, Zhixiang; Zhang, Ziye; Liu, Kai; Zeng, Xiaofei; Han, Xiaoyu (SynOpen, 2023)
A direct oxidative alkylarylation reaction of N-arylacrylamides with simple alkanes for the synthesis of 3,3-disubstituted oxindoles under metal-free conditions was demonstrated. By using PhI(OAc)2 [(diacetoxy)iodobenzene] as an oxidant, a series of 3,3-disubstituted oxindoles bearing different aryl or alkyl substituents were generated in moderate to excellent chemical yields via a radical-initiated alkylation/cyclization process. The reported method features good functional group tolerance and wide substrate range, and provides an effective method for the preparation of various alkyl substituted 3,3-disubstituted oxindoles.
Keywords: oxindoles; alkylarylation; N-arylacrylamide; PhI(OAc)2; metal-free